ANALISIS KUALITAS KIMIA AIR SUNGAI RIUAPA DAN DAMPAKNYA TERHADAP LINGKUNGAN - Elna Soukotta; Robert Ozsaer; Bokiraya Latuamury (JURNAL HUTAN PULAU-PULAU KECIL, 2019)
Riuapa river is an integrated part of Waeriuapa Watershed that usefull for people around the area as agriculture irrigation, livestock, fresh water fish pond, and other domestic use for people activities. As an open watershed ecosystem, that flow into the sea, the river of Watershed was received various input from outside, either from upland to the estuary. Those input were domestic household waste, farming activities waste, and input from land erosion and land slide. The study was conducted to identify water quality through polutant level measurement, in the river and in the flood plain, especially for Chemical polutant element. Red waste, farming activities waste, and input from land erosion and land slide. The study was conducted to identify water quality through polutant level measurement, in the river and in the flood plain, especially for Chemical polutant element. Result of analisys using Statistical Analisys, namely, Factorial Design in Randomized Completly Design (3x2x3), as follows: Location of station in the river and Season factor was significant influence the chemical variable of BOD, COD, Nitrite, and Chlor in the river, and shallow well as well, at the level of beyond National Water Quality Standard, and affected environmental around the area. Changging of upper land cover of Waeriuapa Watershed was significant effected to water debit, fluctuation of rainfall and effected to liquidity process of water quality, that increase of BOD from 2.9 mg/l in dry season to 4.6 mg/l in rainy season; COD from 2.9 in dry season to 21.3 mg/l in rainy season; Nitrite content of 0.0001 mg/l in dry season to 0.0022 mg/l in rainy season.